Pengaruh Proses Pengeringan dan Penambahan Biomassa Tempurung Kelapa Pada Briket Antrasit Terhadap Kadar Zat Terbang dan Kadar Abu - Al Aziz, Putra Habib; Wahyudie, Illham Ary; Yuliyanto, Yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Indonesia is a country rich in natural resources, particularly coal and coconuts. The purpose of this research is to determine the effect of drying processes and the addition of coconut shell biomass to anthracite briquettes on volatile matter content and ash content. A full factorial method was employed in this study, with three factors: drying temperature, drying time, and water-to-molasses ratio. The results show that the coconut shell biomass added to anthracite briquettes significantly affects the volatile matter content. The lowest volatile matter content, 24.8%, was observed in briquette samples dried at 120? for 90 minutes with a water-to-molasses ratio of 4:3. On the other hand, the highest volatile matter content, 28.1%, was produced by briquette samples dried at 100? for 90 minutes with a water-to-molasses ratio of 4:1. The lowest ash content, 41.1%, was found in briquette samples dried at 120? for 60 minutes with a binder ratio of 4:1, while the highest ash content, 35.8%, was observed in samples dried at 100? for 60 minutes with a binder ratio of 4:3.